2011
DOI: 10.1002/pat.1620
|View full text |Cite
|
Sign up to set email alerts
|

Curing kinetics, thermal, mechanical, and dielectric properties based on o‐cresol formaldehyde epoxy resin with polyhedral oligomeric (N‐aminoethyl‐γ‐amino propyl)silsesquioxane

Abstract: The curing reaction and kinetics of o‐cresol formaldehyde epoxy resin (o‐CFER) with polyhedral oligomeric silsesquioxane of N‐aminoethyl‐γ‐amino propyl group (AEAP‐POSS) were investigated by differential scanning calorimetry (DSC). The thermal, mechanical, and dielectric properties of o‐CFER/AEAP‐POSS nanocomposites were investigated with thermogravimetric analysis (TGA), torsional braid analysis (TBA), tensile tester, impact tester, and electric analyzer, respectively. The results show that the activation ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Theoretically, the dielectricity is described by the Debye equation (eq ), where the parameters are number density of dipoles N , electric susceptibility α e , distortion polarization α d , orientation polarization related to the dipole moment μ, Boltzmann constant κ b , and the temperature T 4 . Specifically, for epoxy resins to have an improved low dielectricity, currently available strategies are through introducing low-polarizable groups and/or increasing the molecular free volume ratio. …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the dielectricity is described by the Debye equation (eq ), where the parameters are number density of dipoles N , electric susceptibility α e , distortion polarization α d , orientation polarization related to the dipole moment μ, Boltzmann constant κ b , and the temperature T 4 . Specifically, for epoxy resins to have an improved low dielectricity, currently available strategies are through introducing low-polarizable groups and/or increasing the molecular free volume ratio. …”
Section: Results and Discussionmentioning
confidence: 99%
“…To reduce the dielectricity of a polymer, according to the Debye equation of dielectrics, , two strategies have been intensively explored: decreasing the polarizability and increasing the molecular free volume ratio. , In effect, both the strategies lead to dilution of the dipole density in the polymer. For epoxy resins, through introducing low-polarizable groups such as C–Si and C–F bonds to the host polymers, it is possible to lower ε to 3.0; nevertheless, the polar group generation in polymerization is not eliminated and the lowering of tanδ is usually not significant. By incorporating micro-/nanoporous structures in the polymer matrix, the free volume ratio can be increased significantly, resulting in epoxy resins with ε down to 1.9. The method of incorporating micro-/nanoporous structures, however, is hampered with the difficulty in precise control over the size and distribution of the pores as well as the mechanical properties of the polymers. The existing drawbacks in these strategies make it necessary to find more robust alternative methods for fabricating low dielectric epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…Choi J et al [22] have reported the organic/inorganic hybrid composites from the cubic silsesquioxane epoxy resins of octa(dimethylsiloxyethyl cyclohexylepoxide) silsesquioxane. We have reported the curing kinetics, thermal, mechanical, and dielectric properties for o-cresol formaldehyde epoxy resin with polyhedral oligomeric (N-aminoethyl-g-aminopropyl) silsesquioxane [23].…”
Section: Introductionmentioning
confidence: 99%